Comparative Study of the Antioxidant Activities of Water-Soluble Vitamin E Analogues: Trolox and IRFI - Rafiei, Mahdi; Barzegar, Abolfazl; Asadi, Asadollah (Asian Journal of Chemistry, 2013)
The potent antioxidant activity of a novel synthetic-hydrophilic analogue of vitamin E (IRFI) was comparatively studied with the known water-soluble vitamin E derivative (Trolox). Evaluation of molecular properties indicated the higher hydrophilic property and water solubility of IRFI than Trolox. But Trolox is more planar than IRFI analogue. The spectroscopic behaviour of IRFI and Trolox was almost the same with the maximum absorbance of 295 and 300 nm respectively. Cellular antioxidant and antitoxicity assays showed that both IRFI and Trolox freely permeate across cellular membranes, enabling them to be an effective suppressor of intracellular ROS and to protect cells against toxicity. Reduction of ferric ion was efficient for IRFI as well as Trolox in phosphate buffer solution. Data indicated that every one of IRFI and Trolox molecules enables to reduce two galvinoxyl free radicals not only in polar protic ethanol but also in polar aprotic acetonitrile solvents. Although H elimination process in phenolic hydroxyls of IRFI and TxOH is more feasible to free radical reduction than a-tocopherol but the antioxidant activity of TxOH and IRFI is different that mainly via H atom and electron transfer mechanisms respectively. Interestingly, a-tocopherol locates in the borderline for H atom and electron transfer mechanisms of radical suppressing.